Strategi Guru Dalam Menyiapkan Lingkungan Belajar Pada Pembelajaran Berdiferensiasi di Kelas I Sd Gmit Kuanino I Kota Kupang - Mone, Merianti; Nitte, Yulsy Marselina; Nahak, Roswita Lioba (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Strategy is a general pattern of activities between teachers and students in a teaching and learning activity to achieve the goals outlined. This study aims to determine the teacher's strategy in preparing the learning environment in defaming learning in grade 1 GMIT Kuanino 1 Elementary School in Kupang City. The method used in this study is a type of qualitative research with descriptive methods. The data collection instruments in this study were observation sheets, interview guidelines.The findings of this study indicate that schools experience limitations in infrastructure supporting learning activities, and the diagnostic assessment process has not been effective because of the low understanding of the process. The impact, the teacher has not yet met the needs of students based on their interests and talents. The strategies used by the teacher in preparing the learning environment in differentiating include designing various physical environments and providing individual support and guidance